Latest Fire Protection Innovations for Large-Scale Mining Equipment - Don A. Toth (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Until recently, the fire protection systems used to protect mining equipment were based on generically designed, off the- shelf concepts. These systems were reliant on single agent approaches and were generally comprised of a series of small twenty or thirty pound chemical canisters that would discharge their contents when triggered by thermal detection means. As the equipment grew in capacity, the logic used to increase the protection was to add more chemical canisters to the system. Hydraulic excavators and large-scale mining trucks grew dramatically in size into the 1990?s and beyond; with this growth came the increase in major losses due to fire. This was evidenced throughout this period, and continues to be of great concern today. During this presentation you will learn of the significant changes that have come about as a result of this history. Today, dual-agent products, infrared detection and unit-specific, engineered systems are the primary phrases used when discussing how to best protect this equipment from fire loss. This session is a must for anybody looking to optimally protect their equipment assets and for those looking to renew and/or secure new insurance for high value equipment in the future.